Красные люминофори состава Na1-xAgxY1-xEux(MoO4)2 и K1-xTlxY1-xEux(MoO4)2 - Перепелица, Александр Петрович; Неделько, С. Г. (My University, 1996)
Исследована люминесценция красных люминофоров состава Na1-xAgxY1-xEux(MoO4)2 и K1-xTlxY1-xEux(MoO4)2. Установлена зависимость интенсивности люминесценции от концентрации активатора.

The luminescence of red luminophores composite Na1-xAgxY1-xEux(MoO4)2 and K1-xTlxY1-xEux(MoO4)2 was researched. The dependence of intensity luminescence from comcentration of activator was determined
Keywords: люминесценция; luminescence; красные люминофоры; Na1-xAgxY1-xEux(MoO4)2; K1-xTlxY1-xEux(MoO4)2; получение; red luminophores; preparation; кафедра харчової хімії